2020
DOI: 10.1002/cctc.201902380
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Ligand‐Free Heterogeneous Palladium‐Catalyzed Sonogashira Cross‐Coupling Reaction in Deep Eutectic Solvents

Abstract: The commercially available and cheap Pd/C was found to promote Sonogashira couplings in the environmentally friendly choline chloride/glycerol eutectic mixture in the absence of external ligands. Under heterogeneous conditions, (hetero)aryl iodides were successfully coupled with both aromatic and aliphatic alkynes in yields ranging from 50 to 99 % within 3 h at 60 °C. The aforementioned catalytic system proved to be effective also towards electron‐rich iodides, which are notoriously known to be poorly reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…However, for co‐doped 3 , there was a noticeable difference in the N/C and S/C ratios (i. e., 0.3 and 3.2 %, respectively). We presume that the iodo groups at the 2,5‐positions of the thiophene ring are more reactive than those in the pyridine ring and participate more in the formation of the microporous porous network during the polymerization reaction [37] . Thus, the thiophene units caused the highest microporosity and highest specific surface area in 2 among other polymer networks, as shown above.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, for co‐doped 3 , there was a noticeable difference in the N/C and S/C ratios (i. e., 0.3 and 3.2 %, respectively). We presume that the iodo groups at the 2,5‐positions of the thiophene ring are more reactive than those in the pyridine ring and participate more in the formation of the microporous porous network during the polymerization reaction [37] . Thus, the thiophene units caused the highest microporosity and highest specific surface area in 2 among other polymer networks, as shown above.…”
Section: Resultsmentioning
confidence: 83%
“…The porous networks 1 and 2 had high specific surface areas of 203 and 446 m 2 g À 1 , respectively, while 3 showed a relatively low initial specific surface area of 7 m 2 g À 1 . Given that monomers dramatically alter porosity in polymer networks, [35,36] the larger value of 2 than that of 1 would be attributed to the shape and reactivity of the thiophene linker; [27,37] meanwhile, the combination of both linkers would increase randomness in the structure, which formed mesopores rather than micropores and caused decrease in the surface area of 3. After carbonization, negligible change was found in 1 and 2.…”
Section: Alteration Of Polymer Network By Thermal Carbonizationmentioning
confidence: 99%
“…Capriati et al, reported Suzuki‐Miyaura cross‐coupling reactions utilizing aryltrifluoroborates in DES. Surprisingly, lesser reports on cross‐coupling reactions in DES media are known . In this report of the Suzuki and Sonogashira C−C couplings addition of base in the transition‐metal catalysis was excluded considering green chemistry reaction conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their ability to act also as catalysts and reagents [29,30], DESs have been primarily investigated in extraction and separation processes [31][32][33][34], in material sciences [35], for metal electrodeposition [36], and for the synthesis of heterocycles [37]. Emerging and hot fields of applications are represented by organometallics [38][39][40], metal- [41][42][43][44][45][46][47][48], bio- [49][50][51][52][53], and organo-catalysis [54][55][56][57], electrochemistry [58], photosynthesis [59] and energy technology [60,61]. Building upon our interests in the synthesis of drugs and heterocycles using eco-friendly reaction media like DESs [43][44][45][46][47]55,62,63] and water [64], herein we report the sustainable preparation of several 2-hydroxyphenylbenzimidazole derivatives and the whole synthesis of PZ1 [19] in selected eutectic mixtures.…”
Section: Introductionmentioning
confidence: 99%